2013
DOI: 10.1021/ol4016089
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Approach to Semicarbazone and Hydrazone Derivatives via Imino-isocyanates

Abstract: Isocyanates have a broad spectrum of uses and they are used in the production of many products including polyurethane polymers, coatings, adhesives, paints and foams. While isocyanates are widely studied and well represented in the literature, nitrogen substituted isocyanates are quite rare.Amino and imino-isocyanates are examples of nitrogen substituted isocyanates. Previous work within the group studied the reactivity of these intermediates in the alkene aminocarbonylation reaction, and used hydrazones and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…It should be highlighted that carbazones are typically excellent N -isocyanate precursors: easier to synthesize, stable, often crystalline yet in general more prone than amino-isocyanates to react with nucleophilic amines. 6 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be highlighted that carbazones are typically excellent N -isocyanate precursors: easier to synthesize, stable, often crystalline yet in general more prone than amino-isocyanates to react with nucleophilic amines. 6 …”
Section: Resultsmentioning
confidence: 99%
“…This encouraged us to investigate the generation and reactivity of N -isocyanate precursors with simple nucleophiles. Gratifyingly, the substitution reactions proceeded efficiently under stoichiometric conditions using both hydrazones 6 and hydrazides 7 as blocked N -isocyanates ( Scheme 1 ). A comparison of the conditions below establishes that imino-isocyanates react more readily than amino-isocyanates.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that amphoteric amino‐ and imino‐isocyanates can be formed in situ under mild conditions and engage in high‐yielding alkene cycloadditions6ac and nucleophilic additions,6d,e despite their known tendency to dimerize or oligomerize 7. 8 Hydrazones6bd and hydrazides6a,e are bench‐stable, convenient “blocked” N ‐substituted isocyanate precursors9 that form the desired isocyanates via an equilibrium induced under mild conditions, and then react with nucleophiles such as amines, alcohols, and thiols 6de. Using this reactivity, we developed a cascade substitution/hydroamination sequence allowing rapid assembly of saturated nitrogen heterocycles from hydrazide starting materials 6e.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, there have been no examples of cascade reactions involving either imino‐isocyanates (CNNCO) or amido‐isocyanates [C(O)NNCO] reported to date, and we felt that this extension would significantly broaden the applicability of this approach to aminohydantoins. Thus we first investigated the ability of imino‐isocyanates to engage in cascade reactions, building on our recent report on their substitution reactivity 6d. We were pleased that several hydrazones used as imino‐isocyanate precursors afforded the desired aminohydantoins in the presence of N ‐methyl glycine ethyl ester (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Related reactivity of hydrazone derivatives was studied in detail by Beauchemin and co-workers (Equation 11), 33 who looked at the ability of a variety of substrates and nucleophiles to undergo similar reactions. Notably, this work showed that substitution is possible at room temperature using amines and iminoisocyanate precursors with suitable leaving groups (e.g., LG = OPh).…”
Section: Equation 10 Thermolysis Of Semicarbazones: Addition Of Nuclementioning
confidence: 99%